Three-dimensional printing and digital flow in human medicine: a review and state-of-the-art - Moya Salazar, Jeel (2022)
The use of exponential technologies is changing how people live and interact; this has been called the “Fourth Industrial Revolution”. Within these technologies, 3D printing is playing a leading role, especially in health. In this context, this literature review aims to present the state of the art of 3D printing, its digital workflow and applications in medicine, and the advantages of its use in public health. Consequently, it describes the benefits for the patient and the medical team from a diagnostic stage, a brief history of its development, what is the digital flow when working with a 3D printer, what experiences of its use in medicine, and finally, how this technology used in medicine and public health can be part of the Digital Transformation in Peru.